2020
DOI: 10.1101/2020.06.24.169664
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early cardiac inflammation as a driver of murine model of Arrhythmogenic Cardiomyopathy

Abstract: The study of a desmoglein 2 murine model of arrhythmogenic cardiomyopathy revealed cardiac inflammation as a key early event leading to fibrosis. Arrhythmogenic Cardiomyopathy (AC) is an inherited heart muscle disorder leading to ventricular arrhythmias and heart failure due to abnormalities in the cardiac desmosome. We examined how loss of desmoglein 2 (Dsg2) in the young murine heart leads to development of AC. Cardiomyocyte apoptosis was an early cellular phenotype and RNA-Seq analysis revealed early activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…A recent study in keratinocytes also revealed that ADAM17 inhibition did not alter EGFR signaling (Kugelmann et al, 2022). In mice lacking DSG2, ADAM17 was increased in 2 week old hearts (Ng et al, 2021). Furthermore, increased levels of EGF, indicating an increased EGFR activity, also increased the protein levels of ADAM17 (Santiago-Josefat et al, 2007).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A recent study in keratinocytes also revealed that ADAM17 inhibition did not alter EGFR signaling (Kugelmann et al, 2022). In mice lacking DSG2, ADAM17 was increased in 2 week old hearts (Ng et al, 2021). Furthermore, increased levels of EGF, indicating an increased EGFR activity, also increased the protein levels of ADAM17 (Santiago-Josefat et al, 2007).…”
Section: Discussionmentioning
confidence: 92%
“…A deficiency of tissue inhibitor of metalloproteases 3 (TIMP3), a physiological inhibitor of ADAM17, can result in DCM (Fedak et al, 2004). Finally, in a Dsg2 −/− murine model for arrhythmogenic cardiomyopathy (AC), ADAM17 levels were increased in the hearts of 2 week old mice (Ng et al, 2021).…”
mentioning
confidence: 99%